The dynamics of preventive diplomacy - Kalha, Ranjit Singh 1942- (KW Publishers in association with United Service Institution of India, 2014)
The Dynamics of Preventive Diplomacy is a unique study of one of the more enduring concepts that came to the fore with the end of the cold war. At the heart of the matter is the concern of the international community that symptoms of impending conflict situations must be diagnosed early and treated promptly, much like any disease, so that the world is spared the horrors of unending conflict. While the sentiments of the international community are unexceptional, yet translating them into action is still very controversial. Great powers are not yet prepared to forgo their privileges